Redes Sociais, Facebook e debate político: olhares dos movimentos sociais - Denise Osório Severo; Maria da Graça Luderitz Hoefel; Helena Shimizu (Ciências Sociais Unisinos, 2017)
The purpose of this work is to know the views of members of different social movements about the potential of Facebook and virtual networks as spaces for political debate in order to identify possible interfaces between the different views and the main technology concepts referred to in the literature. It is a participant observation research, qualitative approach. The data derive from interviews made through a semi-structured format, participator observation, field diary and photographic registrations conducted with militants groups of five social movements and different social networks. The results show that Facebook and virtual networks still represent a nebulous field for many social movements, especially the classic ones, which are trying to get along with such networks in order to understand them, considering them as a new way of working and different kind of organization for the struggles. It is possible to observe that there is no agreement concerning the potential of Facebook and virtual networks as spheres of political debate.